Disparate Effects of Lithium and a GSK-3 Inhibitor on Neuronal Oscillatory Activity in Prefrontal Cortex and Hippocampus - Nguyen, Tuan; Fan, Theresa; George, Susan R.; Perreault, Melissa L. (Frontiers in Aging Neuroscience, 2018)
Glycogen synthase kinase-3 (GSK-3) plays a critical role in cognitive dysfunction associated with Alzheimer’s disease (AD), yet the mechanism by which GSK-3 alters cognitive processes in other disorders, such as schizophrenia, remains unknown. In the present study, we demonstrated a role for GSK-3 in the direct regulation of neuronal oscillations in hippocampus (HIP) and prelimbic cortex (PL). A comparison of the GSK-3 inhibitors SB 216763 and lithium demonstrated disparate effects of the drugs on spatial memory and neural oscillatory activity in HIP and PL. SB 216763 administration improved spatial memory whereas lithium treatment had no effect. Analysis of neuronal local field potentials in anesthetized animals revealed that whereas both repeated SB 216763 (2.5 mg/kg) and lithium (100 mg/kg) induced a theta frequency spike in HIP at approximately 10 Hz, only SB 216763 treatment induced an overall increase in theta power (4-12 Hz) compared to vehicle. Acute administration of either drug suppressed slow (32-59 Hz) and fast (61-100 Hz) gamma power. In PL, both drugs induced an increase in theta power. Repeated SB 216763 increased HIP-PL coherence across all frequencies except delta, whereas lithium selectively suppressed delta coherence. These findings demonstrate that GSK-3 plays a direct role in the regulation of theta oscillations in regions critically involved in cognition, and highlight a potential mechanism by which GSK-3 may contribute to cognitive decline in disorders of cognitive dysfunction.